2014
DOI: 10.1021/es405269q
|View full text |Cite
|
Sign up to set email alerts
|

Semivolatile Organic Compounds in Indoor Air and Settled Dust in 30 French Dwellings

Abstract: Semivolatile organic compounds (SVOCs) are ubiquitous contaminants in indoor environments, emanating from different sources and partitioning among several compartments, including the gas phase, airborne particles, and settled dust. Nevertheless, simultaneous measurements in the three compartments are rarely reported. In this study, we investigated indoor concentrations of a wide range of SVOCs in 30 French dwellings. In settled dust, 40 out of 57 target compounds were detected. The highest median concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
105
8
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(133 citation statements)
references
References 79 publications
15
105
8
2
Order By: Relevance
“…This result is consistent with other studies reviewed by Blanchard et al. (), showing that the other measured molecules (DEHP, DINP, and BBP) are usually more present in settled dust than in ambient air. The results are partly in accordance with those found in Germany by Koch et al.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This result is consistent with other studies reviewed by Blanchard et al. (), showing that the other measured molecules (DEHP, DINP, and BBP) are usually more present in settled dust than in ambient air. The results are partly in accordance with those found in Germany by Koch et al.…”
Section: Discussionsupporting
confidence: 93%
“…The detailed sampling and analytical method already has been described by Blanchard et al. (). Filters and foams were extracted together by pressure liquid extraction (PLE) with dichloromethane and analyzed by GC coupled to tandem MS as described by Mercier et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Phthalate esters are frequently detected in water, sediment, air, and dust, 3,4 and humans are exposed to phthalate esters through multiple routes and media. 5 Many studies have reported that phthalate esters and their metabolites are ubiquitous in human body fluids and matrices, including human urine, serum, seminal fluid, breast milk, amniotic fluid, and placenta.…”
Section: Introductionmentioning
confidence: 99%
“…A number of field campaigns have been conducted to measure air concentrations of SVOCs in indoor (Blanchard et al, 2014;Kolarik et al, 2008;Trabue et al, 2008;Wang et al, 2014 andXu et al, 2014) and outdoor environments (Albinet et al, 2007;Chao et al, 2003;He and Balasubramanian, 2010;MacLeod et al, 2007 andXie et al, 2014b). The fate and transport of SVOCs, as well as human exposures to them, can be influenced significantly by gas/particle partitioning.…”
Section: Introductionmentioning
confidence: 99%